2020
DOI: 10.1186/s12933-020-01064-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic steatohepatitis and progression of carotid atherosclerosis in patients with type 2 diabetes: a Korean cohort study

Abstract: Background: There is increasing concern regarding cardiovascular risk in individuals with non-alcoholic fatty liver disease. This study was conducted to evaluate whether hepatic steatosis with or without fibrosis is associated with the progression of carotid atherosclerosis in patients with type 2 diabetes. Methods: From a longitudinal cohort, we enrolled 1120 patients with type 2 diabetes who underwent repeated carotid artery ultrasonography every 1-2 years. Ultrasonographic findings at baseline and after 6-8… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 62 publications
(64 reference statements)
0
20
0
Order By: Relevance
“…Several lines of evidence have shown that NAFLD is associated with an increased risk of cardiovascular events in T2DM patients. Lee et al showed that NAFLD was independently associated with progression of carotid intima-media thickness, as a well-established surrogate marker of subclinical atherosclerosis, in T2DM patients [ 21 ]. In an observational study of 2103 T2DM patients, NAFLD was associated with an increased incidence of cardiovascular events after adjustment for multiple risk factors (HR 1.96, 95% CI 1.4–2.7) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have shown that NAFLD is associated with an increased risk of cardiovascular events in T2DM patients. Lee et al showed that NAFLD was independently associated with progression of carotid intima-media thickness, as a well-established surrogate marker of subclinical atherosclerosis, in T2DM patients [ 21 ]. In an observational study of 2103 T2DM patients, NAFLD was associated with an increased incidence of cardiovascular events after adjustment for multiple risk factors (HR 1.96, 95% CI 1.4–2.7) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies and meta-analysis have found a close association between NAFLD and subclinical atherosclerosis and CVD [ 9 , 12 , 23 , 24 ]. NAFLD is considered as hepatic manifestation of the MetS, and increasing evidence suggested that NAFLD may be both a cause and a consequence of MetS and its components, with insulin resistance (IR) as a common pathophysiological mechanism [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study including 400 individuals in Italy found that individuals at high probability of fibrosis had a 3.9-fold increased risk of vascular atherosclerosis as compared with individuals at low probability of fibrosis [ 5 ]. A longitudinal cohort study on 1120 T2DM showed that hepatic steatosis with fibrosis is independently associated with the progression of carotid atherosclerosis [ 12 ].A retrospective cohort study on 3,185 adult men without carotid atherosclerosis at baseline showed that NAFLD patients with a high NFS and fibrosis-4 scores at baseline had higher risk of subclinical carotid atherosclerosis development [ 9 ], however, this finding is only generalisable to male population. A cross-sectional study with 251 subjects in Malaysian showed that NAFLD and advanced liver fibrosis assessed using FibroScan appeared to be not associated with increased CIMT [ 14 ]; however, given the small sample size, the result may be affected by insufficient statistical power.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 NAFLD is inextricably linked with type 2 diabetes (T2DM), metabolic syndrome, cardiovascular events, and chronic kidney disease and increases the risk of obstructive sleep apnoea, osteoporosis, and hypothyroidism. 3–7 Therefore, the high incidence and concealed health dangers of NAFLD have become a public health issue that should not be ignored.…”
Section: Introductionmentioning
confidence: 99%